2021
DOI: 10.1002/wer.1637
|View full text |Cite
|
Sign up to set email alerts
|

Metallic, metal oxide, and metalloid nanoparticles toxic effects on freshwater microcrustaceans: An update and basis for the use of new test species

Abstract: In this article, we performed a literature review on the metallic, metal oxide, and metalloid nanoparticles (NP) effects on freshwater microcrustaceans, specifically focusing on (i) the main factors influencing the NP toxicity and (ii) their main ecotoxicological effects. Also, given that most studies are currently developed on the standard test species Daphnia magna Straus, we analyzed (iii) the potential differences in the biological responses between D. magna and other freshwater microcrustacean, and (iv) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 120 publications
0
9
0
2
Order By: Relevance
“…In the first step of testing metal nanoparticles as potential animal feed additives, many researchers conduct preliminary nano-toxicological studies to determine the impact of examined nanoparticles on cell cultures (Leng et al 2020 ) or animal models, for example mice (Zhang et al 2008 ; Kesmati et al 2016 ), rats (Tomaszewska et al 2017 ; Mazaheri et al 2019 ; Sanati et al 2019 ; Kociova et al 2019 ; Bidian et al 2021 ; Naz et al 2021 ), worms (Ayech et al 2020 ), insects like Drosophila melanogaster (Pilaquinga et al 2021 ) or in the case of aquatic organisms on water flea, like Daphnia magna (Gong et al 2016 ; Conine and Frost 2017 ), Ceriodaphnia dubia (Li et al 2011 ) or fish (Gutierrez et al 2021 ). The findings obtained for these organisms may be extrapolated on other living beings (Pilaquinga et al 2021 ).…”
Section: Applications Of Nanoparticles As Feed Additives On Animal An...mentioning
confidence: 99%
“…In the first step of testing metal nanoparticles as potential animal feed additives, many researchers conduct preliminary nano-toxicological studies to determine the impact of examined nanoparticles on cell cultures (Leng et al 2020 ) or animal models, for example mice (Zhang et al 2008 ; Kesmati et al 2016 ), rats (Tomaszewska et al 2017 ; Mazaheri et al 2019 ; Sanati et al 2019 ; Kociova et al 2019 ; Bidian et al 2021 ; Naz et al 2021 ), worms (Ayech et al 2020 ), insects like Drosophila melanogaster (Pilaquinga et al 2021 ) or in the case of aquatic organisms on water flea, like Daphnia magna (Gong et al 2016 ; Conine and Frost 2017 ), Ceriodaphnia dubia (Li et al 2011 ) or fish (Gutierrez et al 2021 ). The findings obtained for these organisms may be extrapolated on other living beings (Pilaquinga et al 2021 ).…”
Section: Applications Of Nanoparticles As Feed Additives On Animal An...mentioning
confidence: 99%
“…Based on the literature review of the toxic effects of AgNPs in freshwater microcrustaceans, we found that the majority of the studies have been performed with the cladoceran Daphnia magna , a common and standardized species for acute and chronic ecotoxicity testing ( Baun et al, 2008 ; Gutierrez et al, 2021 ). This is due to its easy availability, rapid reproduction, short lifespan, and sensitivity.…”
Section: Aquatic Ecotoxicity Of Silver Nanoparticlesmentioning
confidence: 99%
“…The feeding type for Cladocera was classified into categories related to the filtration mode of each family (Barnett et al 2007). Daphnids and Moinids use limbs 3 and 4 to perform the filtration (D-filtration), Sidids use their first five limbs in filtering (S-filtration) Bosminids uses active swimming while filtering, with less developed thoracic limbs (B-filtration), Chydorids, Macrothricids and Ilyocriptids use their second limb to scrape food from the substrates (C-filtration) (Gutierrez et al 2021). For Copepoda and Ostracoda, the feeding types were scraper, raptorial and suspension feeders.…”
Section: Functional Traitsmentioning
confidence: 99%